METHOD OF VARIATION OF PARAMETERS FOR THE THIRD-ORDER LINEAR PROPORTIONAL DYNAMIC EQUATIONS - Gülşen, Tuba; Acar, Mehmet (Bartın Üniversitesi, 2023)
The differentiation and integration of an integer order are known as fractional calculus. It is possible to think of the proportional derivative as a generalization of a congruent fractional derivative, which is one of the types of fractional calculus. In this article, utilizing the proportional derivative and its characteristics on the time scale, the method of variation of parameters for the third-order linear nonhomogeneous differential equations is given. Then, an example is provided to illustrate how to apply the provided approach.
Keywords: Software Engineering (Other); Yazılım Mühendisliği (Diğer)